Matematyka
lady96
2017-06-21 14:20:58
zad1 ) 2 2/3 - 1/2 +3 = 6) 5/6 × 4/15 + 7/12 ÷ 7/8= 5)3/4 + 2/3 × (-8/12)= 4) -2 1/2 × (-1/2 - 2/3) = 3)1 5/7 × 3 ÷ (2+2/5) 2)( 1/3 +2/7 ) ÷ (1- 1/9) + 3/7= 1) - 2 2/3 ÷1 3/5 + 1 5/6 × 2 = Daje naj za pomoc
Odpowiedź
ziomek9863
2017-06-21 15:40:48

) 2 2/3 - 1/2 +3 = 2 4/6 - 3/6 + 3 = 5 1/6 6)  5/6 × 4/15 + 7/12 ÷ 7/8= 1/3 × 2/3 + 7/12 × 8/7 = 2/9 + 2/3 = 2/9 + 6/9 = 8/9 5) 3/4 + 2/3 × (-8/12)= 3/4 + 2/3 × (-2/3) =  3/4 - 4/9 = 27/36-16/36 =  11/36 4) -2 1/2 × (-1/2 - 2/3) = -5/2 × (-3/6-4/6) = -5/2 × (-7/6)= 35/12 = 2 11/12 3) 1 5/7 × 3 ÷ (2+2/5) = 12/7 ×3 ÷ 12/5 = 36/7 × 5/12 = 15/7 = 2 1/7 2) ( 1/3 +2/7 ) ÷ (1- 1/9) + 3/7= (7/21+6/21) ÷ 8/9 + 3/7 = 13/21 × 9/8 + 3/7 = =39/56 + 3/7 = 39/56 + 24/56 = 60/56 = 1 4/56 = 1 1/14 1) - 2 2/3 ÷1 3/5 + 1 5/6 × 2 = -8/3 ÷ 8/5 + 11/6 ×2 = -8/3 ×5/8 + 11/3 =  -5/3 + 11/3 = 6/3 = 2

Dodaj swoją odpowiedź